Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physreve.95.032407
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced symmetry breaking far from equilibrium and the emergence of biological homochirality

Abstract: The origin of homochirality, the observed single-handedness of biological amino acids and sugars, has long been attributed to autocatalysis, a frequently assumed precursor for early life self-replication. However, the stability of homochiral states in deterministic autocatalytic systems relies on cross-inhibition of the two chiral states, an unlikely scenario for early life self-replicators. Here we present a theory for a stochastic individual-level model of autocatalytic prebiotic self-replicators that are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 57 publications
0
53
0
Order By: Relevance
“…However, recent findings indicate that intrinsic multiplicative noise may be able to stabilize the homochiral states without crossinhibition-making nonequilbrium auto catalysis a viable mechanism of enantioenriched chirality. 11 The theory of chiral amnesia was another attempt to explain the propagation of asymmetry in solids. In short, the initial imbalance towards larger crystals of a single enantiomer drives more solid to crystallize on the larger crystal.…”
Section: Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent findings indicate that intrinsic multiplicative noise may be able to stabilize the homochiral states without crossinhibition-making nonequilbrium auto catalysis a viable mechanism of enantioenriched chirality. 11 The theory of chiral amnesia was another attempt to explain the propagation of asymmetry in solids. In short, the initial imbalance towards larger crystals of a single enantiomer drives more solid to crystallize on the larger crystal.…”
Section: Propagationmentioning
confidence: 99%
“…This inhibition may be because of the formation of an inactive heterodimer (if the initial ratio of S : R enantiomers is not 1:1, a greater fraction of the minor enantiomer will be extracted into the dimer reservoir). However, recent findings indicate that intrinsic multiplicative noise may be able to stabilize the homochiral states without cross‐inhibition—making nonequilbrium auto catalysis a viable mechanism of enantioenriched chirality …”
Section: Introductionmentioning
confidence: 99%
“…In that work, Frank (1953) suggested that the interplay of autocatalysis combined with what he called mutual antagonism would be a necessary ingredient for reaching complete homochirality. Jafarpour et al (2015Jafarpour et al ( , 2017 invoked the possibility that local fluctuations could yield results that are different from those expected by solving the kinetic rate equations. Fluctuation effects are generally expected to play a role in small compartments, or when concentrations are low.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative advance in chiral physics, chemistry, and mathematics sheds light on the phenomenon of chirality in general and on biological homochirality in particular. Several decades ago Frank developed the mathematical model XII for the spontaneous autocatalytic reaction as the mechanism for the evolution of homochirality [60,61]. Recently it was shown that the origin of molecular homochirality could be attributed to the non-equilibrium state of biological systems.…”
Section: Origin Of Biological Homochiralitymentioning
confidence: 99%
“…The diversity of stereospecific (chiral) phenomena was observed in molecular structures including chirality recognition/sensing [95,96], chirality transfer [97], chirality/helicity induction [98][99][100][101], chirality amplification [102][103][104], chirality breaking [61,105], chirality conflict [106,107], helicity inversion [108][109][110], and chiral phase transitions XVII [111][112][113][114]116]. Progress in the studies of molecular chirality transformation is helpful in resolving three questions.…”
Section: Diversity Of Stereospecific Phenomenamentioning
confidence: 99%